Stabilization of influenza vaccine enhances protection by microneedle delivery in the mouse skin. - Fu-Shi Quan; Yeu-Chun Kim; Dae-Goon Yoo; Richard W Compans; Mark R Prausnitz; Sang-Moo Kang (PLoS ONE)
Background Simple and effective vaccine administration is particularly important for annually recommended influenza vaccination. We hypothesized that vaccine delivery to the skin using a patch containing vaccine-coated microneedles could be an attractive approach to improve influenza vaccination compliance and efficacy. Methodology/principal findings Solid microneedle arrays coated with inactivated influenza vaccine were prepared for simple vaccine delivery to the skin. However, the stability of the influenza vaccine, as measured by hemagglutination activity, was found to be significantly damaged during microneedle coating. The addition of trehalose to the microneedle coating formulation retained hemagglutination activity, indicating stabilization of the coated influenza vaccine. For both intramuscular and microneedle skin immunization, delivery of un-stabilized vaccine yielded weaker protective immune responses including viral neutralizing antibodies, protective efficacies, and recall immune responses to influenza virus. Immunization using un-stabilized vaccine also shifted the pattern of antibody isotypes compared to the stabilized vaccine. Importantly, a single microneedle-based vaccination using stabilized influenza vaccine was found to be superior to intramuscular immunization in controlling virus replication as well as in inducing rapid recall immune responses post challenge. Conclusions/significance The functional integrity of hemagglutinin is associated with inducing improved protective immunity against influenza. Simple microneedle influenza vaccination in the skin produced superior protection compared to conventional intramuscular immunization. This approach is likely to be applicable to other vaccines too.